A Single-Layer S/X- Band Shared Aperture Antenna with MIMO Characteristics at X-Band for Airborne Synthetic Aperture Radar Applications - Raja Babu Bandi; Venkata Kishore Kothapudi; Lakshman Pappula; Rajkumar Kalimuthu; Srinivasa Kiran Gottapu (International Journal of Antennas and Propagation)
New frequencies can be supported with very effective space use by using the shared aperture antenna This work presents on designing a dual-banddual-polarized (DBDP) S/X-band shared aperture antenna (SAA) for synthetic aperture radar (SAR) applications operating at S-band frequency (3.2 GHz) and X-band frequency (9.65 GHz). The single-layer SAA DBDP S-band antenna is designed in a square-shaped patch with coaxial feeding in both vertical and horizontal polarization. The X-band antenna design is in 1 × 3 vertical series with microstrip feeding and arranged at four corners of the proposed antenna. The S-band antenna is mainly used for airborne applications such as air traffic control and surface ship radar. In contrast, the X-band antenna application is maritime vessel traffic control, defense tracking, and vehicle speed detection for law enforcement. To verify the antenna, a prototype is fabricated and measured with s-parameters. The proposed design exhibits that the gain of the S-band is 7.2 dB and for the X-band is 12.4 dB, and the isolation is achieved more than −35 dB, and for this antenna, we achieved a bandwidth of 0.12 GHz for S-band and 0.27 GHz for X-band. However, the X-band antenna is a multi-input and multioutput antenna that is to be validated by using MIMO characteristic parameters such as envelope correlation coefficient (ECC), diversity gain (DG), channel capacity loss (CCL), mean effective gain, and mutual coupling. The MIMO characteristic parameter of X-band antenna values is found to be in a similar manner to both simulated and measured values. For this X-Band antenna, ECC, DG, CCL, and mutual coupling were achieved as below 0.05, 9.5 dB, 0.5 bps/Hz, and −30 dB to −55 dB, respectively. The total size of the antenna is 100 mm × 100 mm × 1.6 mm.